2013
DOI: 10.1007/s40279-013-0067-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Triathlon Performance: Effects of Sex and Age

Abstract: The influences of sex and age upon endurance performance have previously been documented for both running and swimming. A number of recent studies have investigated how sex and age influence triathlon performance, a sport that combines three disciplines (swimming, cycling and running), with competitions commonly lasting between two (Short distance : 1.5 km swim, 40 km cycle and 10 km run) and eight hours (Ironman distance: 3.8 km swim, 180 km cycle and 42 km run) for elite triathletes. Age and sex influences u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 109 publications
(192 reference statements)
1
81
0
13
Order By: Relevance
“…The influence of internal and external factors on pacing may differ between males and females, due to internal (physiological and morphological107) and external (participation rates108) differences between sexes (for review see Lepers et al107). The physiological differences have been attributed to a 12%–15% lower maximal oxygen consumption (VO 2max ),109 5%–10% lower hemoglobin concentration, and ∼8% higher body fat percentage in elite females, as compared with elite males 107,110,111.…”
Section: Factors Influencing Pacing In Triathlonmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of internal and external factors on pacing may differ between males and females, due to internal (physiological and morphological107) and external (participation rates108) differences between sexes (for review see Lepers et al107). The physiological differences have been attributed to a 12%–15% lower maximal oxygen consumption (VO 2max ),109 5%–10% lower hemoglobin concentration, and ∼8% higher body fat percentage in elite females, as compared with elite males 107,110,111.…”
Section: Factors Influencing Pacing In Triathlonmentioning
confidence: 99%
“…The physiological differences have been attributed to a 12%–15% lower maximal oxygen consumption (VO 2max ),109 5%–10% lower hemoglobin concentration, and ∼8% higher body fat percentage in elite females, as compared with elite males 107,110,111. Le Meur et al32 observed that, during a World Cup Olympic-distance triathlon, females spent a greater percentage of total time (45%) above maximal aerobic power when cycling up hills, as compared with males (32%).…”
Section: Factors Influencing Pacing In Triathlonmentioning
confidence: 99%
“…Although this condition occurs in sedentary individuals, athletes (particularly runners) can also be affected [9]. It is anticipated that the prevalence of gluteal tendinopathy in athletes will increase in parallel with the increasing age of society and increasing participation of females in long-distance running and triathlons [10][11][12]. In the USA, the average age of participants in road races is 40 years [10] and more than 43 % of triathletes are over 40 years of age, with females constituting 38 % of all triathletes [12].…”
Section: Introductionmentioning
confidence: 99%
“…For endurance sports such as running, swimming, triathlon or rowing, peak performance was described at the age of ~35 years with a linear decline in performance until the age of ~70 years 2,4,5 . After the age of ~70 years, the performance declined exponentially [1][2][3]5 .…”
Section: Introductionmentioning
confidence: 99%
“…For endurance sports such as running, swimming, triathlon or rowing, peak performance was described at the age of ~35 years with a linear decline in performance until the age of ~70 years 2,4,5 . After the age of ~70 years, the performance declined exponentially [1][2][3]5 . For swimmers, the age-related performance decline in freestyle swimming showed differences regarding the distance and the sex, with a greater decline in long-distance performances such as 1,500-m freestyle and for women compared to men 2,3 .…”
Section: Introductionmentioning
confidence: 99%